PEMILIHAN LAPANGAN BASKET WILAYAH JAKARTA DENGAN MENGGUNAKAN METODE K-NEAREST NEIGHBOR - Andy Wijaya; Desi Arisandi; Bagus Mulyawan (Fakultas Teknologi Informasi Universitas Tarumanagara, 2020)
Finding a Basketball Court is not easy, especially for those who come from outside Jakarta or have minimal information. There are several factors that can influence players to choose a basketball court such as price, distance and facilities. Therefore, the web was made for the recommendation of the selection of basketball courts in Jakarta using the K-NEAREST NEIGHBOR method. This method can recommend the type of field that matches the criteria entered by the court finder.